Indonesian Higher Education of Innovation In Learning English In The Pandemic And New Normal Period - Gabriel Fredi Daar (Universitas Sembilanbelas November Kolaka, 2021)
Innovation of learning activities in universities is a necessity because they are considered as actors of innovation itself. This paper aims to explore higher education innovations in Indonesia during the pandemic and post-pandemic that can be utilized in English learning activities. This research is a literature study by utilizing data obtained from online journals, books, and government regulations as analysis material. Higher education innovations can be seen in the government's new concepts and policies that are relevant to the COVID-19 pandemic. Furthermore, the innovation of learning platforms, including digital learning media, is very appropriate to use in online English learning activities from home. These two major innovations, besides being useful for responding to educational challenges during the pandemic, are also a medium for developing independence in student learning.